Which Origin for Charcoal in Soils? Case-Studies of Environmental Resources Archaeology (ERA) From the Ligurian Apennines, Seventh to the Twentieth Century - Pescini, Valentina (Frontiers in Environmental Science, 2019)
Currently, soils types such as Amerindian “Terra Preta” or “charcoal earth” are considered as archaeological/anthropogenic soils, where explicit human impacts have transformed the patterns, chemistry and shape of the soil. There are several woodmanship practices, poorly visible in archaeological features, that have modified the characteristics of these soils and sediments. Today, these activities are difficult to identify, especially those relating to the multiple management of environmental resources (e.g. agro-sylvo-pastoral systems) due to their abandonment and disappearance in southern Europe during the 19th and 20th centuries. Describing a selection of researches conducted by the Laboratory of Archaeology and Environmental History (LASA) team in the Ligurian Apennines, this article explores the potential role of Environmental Resources Archaeology (ERA) and site(s)-level historical ecology approaches to past land use and woodmanship practices characterisation. In particular, focus is given to the practices derived from analysis of microcharcoal in the soils and sediments. Such an approach involves and combines the use of multiple sources (documentary, oral, observational and bio-stratigraphic sources), a regressive analysis method and a strong spatial and social contextualization.